Nauczanie kompetencji językowych w układzie zintegrowanym, czyli praktyka w praktyce - Seretny, Anna; Lipińska, Ewa (Postscriptum Polonistyczne, 2020)
The cognitive approach in teaching points out clearly to the necessity of integrating language skills in didactic process. Such skills in everyday situations usually appear together: we read in order to write down certain information, we listen to someone’s utterance in order to repeat it to someone else, we write something for someone else to read it etc. Such attitude in teaching imitates a real character of natural communication that combines different types of skills in one multidimensional entity. Methodological materials say nothing or very little on the necessity of integral teaching of the parts of language system that are connected even closer than language skills. No statement can be produced if we do not know the words that this statement should contain and we do not know the rules that must be followed to put these words together. We also need to be able to spell and write down the words correctly in order to make our statement understandable. The article discusses the idea of integrated teaching of the parts of language system along with highlighting its advantages. It is also going to be proved that due to such approach in teaching a learner has numerous and various contacts with language materials, which according to Craik and Lockhart (1971) enhances the process of remembering learnt material.